Analisis Kebutuhan Guru Dalam Menggunakan AI Sebagai Pendukung Media Pembelajaran Matematika Tingkat MA - Devi, Natalia Chyntia; Nurhidayati, Siti; Sugiman; Purwoko, Riawan Yudi (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
This study aims to analyze the needs of Madrasah Aliyah (MA) teachers in Purworejo Regency in utilizing artificial intelligence (AI) as a medium for learning mathematics. A descriptive qualitative approach was used with a data triangulation method to increase the validity and reliability of the study. Data were collected through questionnaires, in-depth interviews, and documentation involving 10 mathematics teachers with various age backgrounds, teaching experiences, and levels of knowledge about AI. The results showed that the majority of teachers (80%) were familiar with AI, while the rest were still less familiar. The most frequently used AI application was Geogebra (40%), followed by Canva and Quizizz (each 20%). The main obstacles faced by teachers were the lack of adequate facilities (70%), time constraints in learning AI (10%), limited school budget (10%), and low understanding of AI (20%). In addition, teachers need ongoing technical training, AI implementation guidance, and infrastructure support, such as internet access and hardware. This study concluded that intensive training, procurement of technology facilities, and collaboration between schools and the government are essential to optimize the use of AI in mathematics learning. These findings contribute to the development of technology-based education policies for Madrasah Aliyah.